Unusual presentation of follicular thyroidcarcinomaas mandibular metastasis - K Dave, Pranav; M, Puranik; Jain, M; Mishra, R; Jain Singhai, M; Lakra, R; Rajak, Y; A, Wandre; Satpathy, S; Gaur, BS (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2018)
Primary carcinoma of thyroid presenting as mandibular metastasis is a rare incidence. Most of the time patient presents with various other symptoms due to hematogenous spread of primary neoplasm. We are presenting a rare case where metastatic lesion of mandible was the presentingfeature and the patient was then subsequently diagnosed to have primary follicular carcinoma of thyroid.